Effects of Property Rights on Entrepreneurship Development in the CEMAC Sub-Region - Vukenkeng Andrew Wujung (Universitas Islam Nahdlatul Ulama Jepara, 2023)
Objective: This article sought to investigate the effects of property rights on entrepreneurship development in the CEMAC Sub- region. Research Design & Methods: Data for this study was collected from the World Governance Indicators (WGI) for the six indicators of governance and World Bank data for entrepreneurship development and control variables. Pooled Ordinary Least Squares estimation technique was used to estimate the parameters of the model. Findings: The findings from the data analysis revealed that there was a negative and significant effect of democracy (captured by voice and accountability index) on entrepreneurship development in CEMAC. In accordance with theoretical expectation, results from data analysis further revealed that there was a positive and significant effect of government effectiveness on entrepreneurship development in the sub region. Results from the pooled OLS estimation showed that there was a negative and significant effect of control of corruption on entrepreneurship development in CEMAC. Contribution & Value Added: The fourth indicator of institutional quality used in this work is political stability. Thus, an improvement of public services by reducing bureaucratic bottlenecks, improvement in the fight against corruption and increasing the level of investments could enhance entrepreneurship development in the sub-region.